Viability of fusarium graminearum in stored wheat seeds Viabilidade de fusarium graminearum em sementes de trigo durante o armazenamento - Neto F.X.B.T. (2007)
© 2007, Universidade Estadual Paulista (UNESP). All rights reserved.Wheat head blight disease intensity has increased under notill, management with the consequence of increasing the incidence of the causal agent of scab in seeds. Wheat seeds of Fundacep 36 cultivar with 29.8% natural incidence of Fusarium graminearum, were stored in braided polypropylene bags, in climatic chamber at temperature between 18 and 20ºC and partial control of air relative humidity, for 12 months. The objective of this work was to quantify the fungus viability according to the storage time. Seed testing was performed every two months, during 14 months. In each assessment time 400 seeds were taken which were submitted to the test using as substratum the culture medium ¼ strength potato-sucrose-agar + streptomycin. Seeds were incubated during seven days at 25°C ± 2 °C temperature and photoperiod of 12 hours. Taking into consideration the decrease of viability according to the storage time, it is suggested that the wheat seed health test to detect the presence of F. graminearum should be performed in a short period of time before seeding, to decide whether to treat or not the seeds with specific fungicide to control the pathogenic fungus.